Answer :

Given:

⇒ (1+i)z=(1-i)

Dividing with (1+i) on both sides we get,

⇒

⇒

⇒

We know that i^{2}=-1

⇒

⇒

⇒

⇒ z=-i

∴ Thus proved

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

Polar & Euler Form of Complex Numbers on Argand Plane32 mins

Interactive Quiz Time - Polar & Euler Form of complex number58 mins

Modulus & Conjugate of Complex Number | Ready for a Quiz?48 mins

Practice session | Argument of complex numbersFREE Class

Special Quiz on Argument of complex numbersFREE Class

Polar & Euler Form of Complex Number on Argand Plane58 mins

Questions Based on Polar & Euler Form of Complex Number63 mins

Questions on Modulus & Conjugate of Complex Number62 mins

Get in the world of Complex Numbers55 mins

Discussion | Miscellaneous Exercise | NCERT Chapter 5| Complex Numbers47 mins

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

Evaluate.

RS Aggarwal - MathematicsEvaluate

RS Aggarwal - Mathematics

If (x + iy)^{1/3} = (a + ib) then prove that = 4 (a^{2} – b^{2}).

If then show that

RD Sharma - MathematicsProve that i^{53} + i^{72} + i^{93} + i^{102} = 2i.